A collaborative application of design thinking and Taguchi approach in restaurant service design for food wellbeing. Issue 2 (5th October 2021) - Rejikumar, G.; Aswathy, Asokan-Ajitha; Jose, Ajay; Sonia, Mathew
Abstract : Purpose: Innovative restaurant service designs impart food wellbeing to diners. This research comprehends customer aspirations and concerns in a restaurant-dining experience to develop a service design that enhances the dining experience using the design thinking approach and evaluates its efficiency using the Taguchi method of robust design. Design/methodology/approach: The sequential incidence technique defines diners' needs, which, followed by brainstorming sessions, helped create multiple service designs with important attributes. Prototype narration, as a scenario, acted as the stimulus for evaluators to respond to the WHO-5 wellbeing index scale. Scenario-based Taguchi experiment with nine foodservice attributes in two levels and the wellbeing score as the response variable helped identify levels of critical factors that develop better FWB. Findings: The study identified the best combination of factors and their preferred levels to maximize FWB in a restaurant. Food serving hygiene, followed by information about cuisine specification, and food movement in the restaurant, were important to FWB. The experiment revealed that hygiene perceptions are critical to FWB, and service designs have a significant role in it. Consumers prefer detailed information about the ingredients and recipe of the food they eat; being confident that there will be no unacceptable ingredients added to the food inspires their FWB. Research limitations/implications: Theoretically, this study contributes to the growing body of literature on design thinking and transformative service research, especially in the food industry. Practical implications: This paper details a simple method to identify and evaluate important factors that optimize FWB in a restaurant. The proposed methodology will help service designers and technology experts devise settings that consider customer priorities and contribute to their experience. Originality/value: This study helps to understand the application of design thinking and the Taguchi approach for creating robust service designs that optimize FWB.